Taṭwīr Mahārāt al-Istima’ min Khilāl Manhaj al-Ta'allum al-Qā’im 'ala al-Mushkilāt bi Wasāil al-I'lām al-Tilifizyūni al-Tafū'uli - Lubis, Arbonas; Purba, Abdur Rahman (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
The aim of this study is to explain the implementation of problem-based learning (PBL) in developing listening skills (maharah istima’) using television as a medium at the As-Sunnah Islamic College, Deli Serdang. This research employs a qualitative method with a phenomenological approach. Data collection techniques include observation, interviews, documentation, and data analysis, which encompasses data reduction, data analysis, and drawing conclusions. The focus of the study is on the planning, implementation, and evaluation of learning activities through the application of problem-based learning to enhance maharah istima’ using television as a medium. The findings indicate that problem-based learning in developing maharah istima’ with television as a medium begins with the preparation of a semester learning plan, which is a crucial step to ensure that the learning process is structured and aligned with the intended learning outcomes. The implementation consists of five stages: (1) problem orientation by explaining the thematic issues using television broadcasts; (2) organizing students into small groups; (3) guiding students, either in groups or individually, to gather information; (4) developing solutions, where each group presents their analysis and proposed solutions; and (5) evaluating the learning process by both lecturers and students. الهدف من هذه الدراسة هو شرح مفهوم التعلم القائم على حل المشكلات في سياق تحسين مهارات الاستماع من خلال استخدام وسائل الإعلام التلفزيونية في جامعة السنة الإسلامية  بدلي سردانج، تستخدم الدراسة منهجية البحث النوعي، باستخدام إطار الظواهر، حيث تشمل تقنيات جمع البيانات الملاحظة والمقابلات والتوثيق وعملية تحليل البيانات متعددة الأوجه التي تشمل تقليل البيانات والتحليل المنهجي وصياغة الاستنتاجات. ركز هذا البحث على تخطيط وتنفيذ وتقييم الممارسات التعليمية التي تتضمن التعلم القائم على حل المشكلات بهدف النهوض بالمهارة المنشودة من خلال وسيلة التلفزيون. تشير نتائج البحث إلى أن المراحل الأولى من تطوير التعلم القائم على حل المشكلات لتحسين استخدام وسيلة التلفزيون تبدأ بصياغة خطة التعلم للفصل الدراسي، وهي خطوة مهمة في ضمان توافق عمليات التعلم المنظمة مع النتائج التعليمية المحددة مسبقًا. يتم تفعيل العملية من خلال خمس مراحل مختلفة: تتضمن المرحلة الأولية توجيه المشكلات، حيث يتم شرح المشكلات الموضوعية من خلال البث التلفزيوني؛ تتضمن المرحلة الثانية تنظيم الطلاب في عدة مجموعات صغيرة؛ المرحلة الثالثة توفر التوجيه للطلاب، إما بشكل جماعي أو فردي، لغرض جمع المعلومات؛ المرحلة الرابعة، المعروفة باسم تطوير النتائج، تتطلب من كل مجموعة تقديم نتائجها التحليلية والحلول المقترحة؛ وتشمل المرحلة الخامسة تقييم التعلم العملية التي أجراها كل من المحاضرين والطلاب.